2023
DOI: 10.1161/atvbaha.122.319025
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Valvular Carditis Requires Endothelial Cell TNFR1 Expression

Abstract: BACKGROUND: Inflammation is a key driver of cardiovascular pathology, and many systemic autoimmune/rheumatic diseases are accompanied by increased cardiac risk. In the K/B.g7 mouse model of coexisting systemic autoantibody-mediated arthritis and valvular carditis, valve inflammation depends on macrophage production of TNF and IL-6. Here, we sought to determine if other canonical inflammatory pathways participate and to determine whether TNF signaling through TNFR1 on endothelial cells is required f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…We have shown that TGFβ signaling via the TGFβR2 on ECs does not affect valve disease progression, but it remains possible that TGFβ action on fibroblasts regulates disease progression. 7 Future lymphatic inhibitor and genetic studies (including macrophage-and fibroblast-specific knockouts) with discrete timing considerations will be needed to test these hypotheses and to understand more fully the functional roles of lymphatics, fibroblasts, and macrophages in the inflamed mitral valve.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that TGFβ signaling via the TGFβR2 on ECs does not affect valve disease progression, but it remains possible that TGFβ action on fibroblasts regulates disease progression. 7 Future lymphatic inhibitor and genetic studies (including macrophage-and fibroblast-specific knockouts) with discrete timing considerations will be needed to test these hypotheses and to understand more fully the functional roles of lymphatics, fibroblasts, and macrophages in the inflamed mitral valve.…”
Section: Discussionmentioning
confidence: 99%